The silver linings playbook - Quick, Matthew 1973-
The story of a man who has lost everything, his house, his job, his wife, and how he creates his own silver linings from the bonds he forms with his family and friends
Property of Weinstein Co. 2008
Based on the novel by Matthew Quick
For your consideration 2012"--Cover
Best adapted screenplay"--Cover
Keywords: Divorced men / Drama; Depression, Mental / Drama; Man-woman relationships / Drama; Motion picture plays; Depression, Mental; Divorced men; Man-woman relationships; Drama; Screenplays; Drehbuch